Fractions: teachers' knowledge and their contribution to the teaching of fourth grade students in Chilean schools. (Innovaciones Educativas, 2023)
Fractions are a complex mathematical subject, difficult to learn and to teach. Previous studies suggest that student learning may be limited by teachers' understanding of fractions. The objective of this study is to examine the extent to which teachers' knowledge in association with socioeconomic status, students' prior knowledge, and the level of mathematics knowledge obtained in schools contributes to students' learning achievement in fractions. Using a quantitative methodology, the study instruments were structured tests with closed questions applied to 714 fourth grade students and 23 teachers from 23 Chilean schools. The data are analyzed using multilevel models. The results show that of the variability observed in the conceptualization of fractions, 76% could be attributed to student level variables, while the remaining 24% could be attributed to school level variables. The variance between schools could be explained 26% by teacher knowledge and 8% by socioeconomic level. This means that teacher knowledge, alone or in combination with other factors, explains about 6% of the total variability in student progress, with a significance of 5%. The level of mathematical knowledge observed in the schools is not significant. In conclusion, the present study reports that teacher knowledge contributes to student learning achievement in addition to the effect of socioeconomic level.
Keywords: Primary school teachers; math teaching; learning; education; mathematics